Pesquisa-ação sobre a ação docente na construção de uma prática dialógica de leitura - Kobashigawa, Elizabeth Kasue Oshiro (2011)
This investigation is carried out in the area of Applied Linguistics (Celani, 1998/2004; Moita Lopes, 2006) and is part of a larger Project developed by a research group called GEIM (Study Group of Indeterminacy and Metaphor), under the supervision of Dr. Mara Sophia Zanotto, and whose researchers investigate a dialogic practice of critical literacy in an actual context of language use with actual readers. The methodology employed was that of qualitative, interpretive nature (Bortoni-Ricardo, 2008), by means of which an action research was carried out, aiming at investigating my own pedagogic practice in reading events experienced by the focal group. The dialogic practice which is investigated is the Group Think Aloud (Zanotto,1998), at one time a pedagogic experience and a research technique that values readers‟ subjectivities and allows for the construction of multiple readings. The theoretical discussion covered: the actual reading tradition in school contexts; traditional reading constructs as well as cognitive models. Furthermore, I also dealt with the notion of reading as an event and social practice (Bloome, 1983; Moita Lopes, 1996) and literacy studies (Soares, 1998). Also the contributions of Vygotsky (1934), Bakhtin (1992) and Freire (1970) in the field of education were discussed. Data generation was completed with a focal group (Gatti, 2005), composed of 9 students of the second year of High School, studying in a Public School. Data analysis indicates the following results: 1. My attitude in the classroom underwent some meaningful changes since I took on the role of a mediator and of an agent of literacy, listening to my students and providing the conditions for them to interact among themselves; 2. The Group Think Aloud allowed for the construction and negotiation of readings in students‟ social interactions. Besides, participants had a responsive attitude during the reading events